Data Structures and Program Design Using C++ - Malhotra, D; Malhotra, N (Mercury Learning & Information, 2019)
Data structures provide a means to manage large amounts of information such as large databases, using SEO, and creating Internet/Web indexing services. This book is designed to present fundamentals of data structures for beginners using the C++ programming language. Practical analogies using real world applications are integrated throughout the text to explain the technical concepts presented. Features:- Covers data structure fundamentals using C++- Numerous tips and practical applications enhance understanding of concepts.